2011
DOI: 10.1177/0887403411418105
|View full text |Cite
|
Sign up to set email alerts
|

Incarcerated Fathers

Abstract: Prior research indicates that strong family support can play an important role in helping men and women transition from prison to home and can actually reduce the likelihood of recidivism. Assuming traditional roles within a family, such as parent or spouse, can also aid in the reentry transition process and has been linked to positive outcomes after release. Using data from a longitudinal study of fathers returning to the community after a period of incarceration, this article examines how the relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(28 citation statements)
references
References 31 publications
(51 reference statements)
1
23
0
4
Order By: Relevance
“…Men maintaining family relations may have lower recidivism and become more aware of parenting responsibilities (Roy & Dyson, 2005). Maintaining father-child relations during incarceration relates to continued fathering postrelease (Roettger & Swisher, 2013;Turney & Wildeman, 2013) and better reentry success for fathers (Visher, 2013;Visher et al, 2013). Understanding the experiences of incarcerated fathers may present an underutilized pathway for more successful rehabilitation and eventual reintegration.…”
Section: Parenting and Incarcerationmentioning
confidence: 99%
“…Men maintaining family relations may have lower recidivism and become more aware of parenting responsibilities (Roy & Dyson, 2005). Maintaining father-child relations during incarceration relates to continued fathering postrelease (Roettger & Swisher, 2013;Turney & Wildeman, 2013) and better reentry success for fathers (Visher, 2013;Visher et al, 2013). Understanding the experiences of incarcerated fathers may present an underutilized pathway for more successful rehabilitation and eventual reintegration.…”
Section: Parenting and Incarcerationmentioning
confidence: 99%
“…In Visher’s (2013) study, assuming traditional roles within a family, such as father or parent, could also aid in the reentry transition, with further links to positive outcomes upon release. Using longitudinal data on fathers’ returning to the community post-incarceration, Visher (2013) examined how the relationship between fathers and their children might influence aspects of life for recently released fathers. Analyses confirmed that fathers who had regular contact with their children before reentry and good family support overall were more likely to be attached to their children.…”
Section: Literature Review With Findingsmentioning
confidence: 99%
“…More frequent family visits while incarcerated both delay and reduce recidivism once an inmate is released (Bales & Mears, 2008). Contact with children during incarceration predicts a father’s level of attachment to them postrelease (Visher, 2013) and commitment to children may help released inmates desist from crime through the transition into an active father role (Uggen, Manza, & Behrens, 2004). Furthermore, the higher level of attachment that results from contact with children during incarceration has been found to predict a father’s postrelease work hours and mental health, as well as to reduce recidivism and parole violations (Bahr et al, 2005; Visher, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Contact with children during incarceration predicts a father’s level of attachment to them postrelease (Visher, 2013) and commitment to children may help released inmates desist from crime through the transition into an active father role (Uggen, Manza, & Behrens, 2004). Furthermore, the higher level of attachment that results from contact with children during incarceration has been found to predict a father’s postrelease work hours and mental health, as well as to reduce recidivism and parole violations (Bahr et al, 2005; Visher, 2013). Although contact may be harmful for children in certain circumstances (Eddy & Reid, 2003), research generally finds that incarcerated father–child contact has the potential to improve outcomes for fathers and children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation